Handbook of political Islam in Europe: activities, means, and strategies from Salafists to the Muslim Brotherhood and beyond - Jäger, Thomas; Thiele, Ralph (Springer Handbooks of Political Science and International Relations, 2024)
Part I: Framework -- Introduction -- Islamism and the Political Order -- A Critical Assessment of Political Islam and Political Islamism -- Political Islamism – A Vital Hybrid Threat/Challenge -- Proponents of Political Islam in the European Union Institutions -- Salafism in Germany: Democracy, and Resilience -- Islam – A Liberal, Intellectually Challenging Partner for Europe? -- The Ideal of an Islamic Society -- Secular Turn in the Middle East: Findings from Values Survey -- Conclusion: A European Response? -- Part II: Actors -- Diyanet in Europe -- How Qatar Became an Actor in the Spread of Political Islam in Europe -- Saudi Arabia and Europe: Demystifying the Threat -- Revolutionaries at Home, Revolutionaries Abroad: Iran and its Networks in Europe -- Political Islam in Exile: Transformation of the Egyptian Muslim Brotherhood After the Military Coup of 2013 -- The Muslim Brotherhood in Europe: A General Framework -- Salafist Movements in Europe: Between Local and Transnational Mobilizations -- The Milli Görüş Movement in Europe: Context, Activities and Strategies -- Tablighi Jamaat in Europe -- Al Qaeda and the Islamic State: The Jihadi War on Christians Comes to Europe -- Part III: Surveys -- Political Islam in Austria -- Political Islam in Belgium: From Third-Country Activism to the Islamicization of the Political Debate -- Hybridizing Islam in the Balkans: The Rise of Salafi-Hanafism in Bulgaria -- Political Islam and Islamism in Europe – French Perspectives -- Political Islamism in Germany -- Political Islam in Greece: An Elusive Threat? -- Islamism in Italy: The Muslim Brotherhood Network and its Allies -- The Muslim Brotherhood and Other Organisations in the Netherlands -- A European Exception? Political Islam and Radical Islamism in Portugal -- Evolution of Political Islam in Romania at the Beginning of the 21st Century -- Contemporary Islamism in Spain: A Landscape Dominated by the Muslim Brotherhood -- Political Islamism – The Case of Sweden and Denmark -- The Muslim Brotherhood in Switzerland -- Shifting Relations Between Islamic Non-State and State Actors in Turkey -- Mainstream Islamism in Britain: Advocacy and Agitation.-Political Islam and Islamism in the Western Balkans -- Comparative Summary. .